Dynamic Routing and Operational Controls in Workflow Management Systems - Kumar, Akhil; Zhao, J. Leon (Management Science, 1999)
Businesses around the world are paying more attention to process management and process automation to improve organizational efficiency and effectiveness. In this paper, we describe a general framework for implementing dynamic routing and operational control mechanisms in Workflow Management Systems (WMSs). The framework consists of three techniques: workflow control tables, sequence constraints, and event-based workflow management rules. Our approach offers several unique features that are missing in commercial workflow management systems: (1) it provides more flexibility in process modeling and control; (2) it permits rework on an ad hoc basis; (3) it handles exceptions to routing and operational controls; and (4) it exploits parallelism to increase system throughput and response time. Finally, the workflow management techniques are applied to the case of consumer loan management and compared with other approaches based on static routing.